Daily soil carbon dioxide flux under different tillage conditions - Törő, Ágnes; Ragán, Péter; Rátonyi, Tamás; Kith, Károly; Harsányi, Endre (Acta Agraria Debreceniensis, 2019)
Over the last few years, warming of the atmospheric layer near Earth's surface is increasingly experienced and researchers have also established that concentration of numerous greenhouse gases have risen over the past two centuries value. Change is basically a legitimate process - considering atmospheric concentration as well - but the change experienced during the past centuries could not have become this critical without the contribution of human activity. Due to the nature of the greenhouse effect, the result of a very fragile, complex process is experienced currently on Earth, which can be significantly unbalanced even by a slight change. Carbon dioxide emitted from the soil is involved in the global cycle and has an impact on the greenhouse effect. The rise in soil respiration may result in the further intensification of warming. In the scope of the present study, it was examined how carbon dioxide emissions of the soil evolve over a day. The results have been established based on the comparison of the effects of different parts of the day, tillage methods and irrigation.